Damping behavior of synthetic graphite beams - Pardini, Luiz Cláudio (2006)
The main objective of this work was to obtain the damping factor as well as the elasticity modulus (E) of two kinds of synthetic graphite (HLM and ATJ), using the modal analysis technique. Prismatic beams of square section (~ 11 x 11 mm) and length over thickness ratio (L/t) of about 22.7 were tested in the free - free boundary condition. The first four modes of vibration were taken into account in the non-destructive evaluation of the materials. In addition, numerical simulations were also carried out in this investigation. The agreement between the theoretical and the experimental results was quite good. The average values of E and for the HLM graphite were 20% and 90% higher, respectively, than those presented by the ATJ graphite, indicating that the HLM graphite has, proportionally, more damping mechanisms than the ATJ graphite.